James Lockhart, C. M. Stafford Poole & Lisa Sousa: The Story of Guadalupe. Luis Laso de la Vega’s Huei Tlamahuiçoltica of 1649; C. M. Stafford Poole: Our Lady of Guadalupe. The Origins and Sources of a Mexican National Symbol, 1531-1797 - Canger, Una (Tidsskriftet Antropologi, 2000)
Anmeldes af Una Canger James Lockhart, C. M. Stafford Poole & Lisa Sousa (eds. & translators): The Story of Guadalupe. Luis Laso de la Vega’s Huei Tlamahuiçoltica of 1649. 122 C. M. Stafford Poole: Our Lady of Guadalupe. The Origins and Sources of a Mexican National Symbol, 1531-1797.